Mobile application for meet up hosting and gathering - Choong, Win Shen (2022)

(untitled)
This project is a mobile application development project that facilitate users in meeting up with stranger. Some of the problems with traditional dating application can be resolved by this proposed project, where user could find it easy to use the application and meet up with others in real person easily. There will be some features assisting user in scheduling and initiating a meet up such as host, join or accept application of a meet up. This will change the way of people engage with each other differently, unlike any other traditional dating applications. Business owner can now take a part in it for their business promotion with booking and profiling function. This project is developed with Extreme Programming methodology which will be easier for an individual or small team. The technology for backend will be using Android studio in Java language, while Firebase will be the main cloud database for any data of users in the application. This project is initialized in Jan 2021 for the first part and it is proceeded in Jan 2022 for the second part.